Treatment of multidrug‐resistant gram‐negative bacilli after solid organ transplant: Outcomes and complications. Issue 1 (7th October 2020) - Heldman, Madeleine R.; Guo, Kexin; Nelson, Brett; Babu, Tenzin; Ison, Michael G.
Abstract: Background: Infections caused by multidrug‐resistant gram‐negative bacilli (GNB) cause significant morbidity and mortality in solid organ transplant (SOT) recipients. Methods: We retrospectively collected data from all SOT recipients at a single center from 1 January 2007 to 15 April 2017 treated for infections caused by multi‐drug‐resistant GNB. This study examined the effects of specific antibiotics on nephrotoxicity, neurotoxicity, 30‐day mortality, and length of stay in the hospital and intensive care unit. Results: A total of 225 infections were identified among 143 patients. Carbapenem‐sensitive organisms were present in 112 (49.8%) infections and were associated with decreased 30‐day mortality (OR 0.35, 95% CI 0.16‐0.75). Neurotoxicity was associated with polymyxin use with an 8% increase in odds of neurotoxicity per day of exposure ( P =.03). There was no relationship between nephrotoxicity and any individual antibiotic class. Increased hospital length‐of‐stay occurred among patients exposed to aminoglycosides (β‐statistic = 0.48 (0.23); P  = .04), while there was no relationship between antibiotic class and intensive care unit (ICU) length‐of‐stay. Mortality at 30 days occurred in 37 infections (16%). Carbapenem exposure was associated with decreased 30‐day mortality (OR 0.93; 95% CI 0.90‐0.98; P  = .02). No other antibiotic class had a significant impact on 30‐day mortality. Conclusions: Carbapenems appear to be a safe and effective treatment for solid‐organ transplant recipients with infections caused by carbapenem‐sensitive multidrug‐resistant GNB; treatment of carbapenem‐resistant gram‐negatives remains challenging.